EKSPLOITASI PEKERJA ANAK DI INDONESIA DAN REKONSTRUKSI ARAH KEBIJAKAN SOSIAL - Miftahul Jannah (KOMUNITAS, 2017)
The children are persons who have the age under 18-years old who havestill the right to be protected from life-threatening matters, from acts of exploitation, and the things that interfere their future. Remembering that the childhood is a growth process, both physical and mental, ideally children should avoid the various behaviors that interferetheir growth. Therefore, children need to be guaranteed their rights, and play. In this paper, the writer wants to describe the forms of exploitation of children such as the loss of children’s rights so they must go the world of work due to poverty problems which become main foundation of children to participate in fulfilling their needs. The factors of exploitation are certainly due to the lack of understanding of the head of the family about the importance of children’s education. Therefore it is important to reconstruct the social policy purposes of the children, in order to avoid exploitation actions which can disturb the growth of a children’s lives, by the reconstruction of social policy of the government, it is able to restore the rights of children in life, so that the fulfillment of all needs and the creation of welfare for children.